EFISIENSI TEKNIS USAHA TERNAK AYAM BROILER POLA KEMITRAAN DI KABUPATEN LIMAPULUH KOTA - Dira Asri Pramita; Nunung Kusnadi; Harianto Harianto (Jurnal Agribisnis Indonesia, 2017)
Due to the high cost of investment in broiler production and the risk involved, various types of lease arrangement in broiler production exist in Indonesia. Two of the best known arrangement include the contract system and the informal profit sharing system. The difference in these two types of arrangement lies in the degree of cooperation which influence their technical efficiency. This study aims to measure the technical efficiencies of broiler farms with the contract system and the profit sharing system. This study also analyzed the basic determinants of the technical efficiency, as well as the socio-economic variables that affect business performance. Cross section data was collected from Limapuluh Kota district between July to September 2015. The purposive  sampling technique was used to identify 87 farmers of which 50 were involved in the contract system arrangement while 37 were involved in the profit sharing arrangement. The data was analyzed using the Cobb-Douglas Stochastic Production Frontier. The results showed that the type of lease arrangement affects the level of technical efficiency. When compared, the technical efficiency of contract system arrangement was higher than that of the informal profit sharing arrangement. The age and experience of broiler farmers significantly influenced the level of technical efficiency. However, while age was positive experience was negative.